Bringing agency back in: Disentangling the complexities of Sri Lanka's default - De Silva, Shakthi (Taylor and Francis, 2025)
This chapter investigates the primary cause behind the economic default of Sri Lanka in April 2022, challenging the predominant epistemological narratives that trace the crisis to external factors such as the COVID-19 pandemic and the alleged Chinese debt trap. It argues that while these exogenous variables may have exacerbated the situation, the primary cause for the island’s default was the flawed policies adopted by Sri Lankan politicians. Having conclusively proven the role played by domestic policies, the chapter extends its analysis to the broader South Asian region, warning against the tendency to absolve local authorities who attribute economic crises to external factors/developments alone. By doing so, the chapter advocates for greater accountability and astute policymaking to mitigate the emergence of future crises. The case of Sri Lanka also serves as a cautionary tale for other peripheral South Asian economies, as the prevailing tendency to blame external actors, such as the International Monetary Fund (IMF), provides policymakers future opportunities to exploit the public’s remissness.
Keywords: Sri Lanka; IMF; economic sovereignty; economic policies; decision making